ANALISIS PENGARUH HARGA, KUALITAS PRODUK, DAN LOKASI TERHADAP LOYALITAS PELANGGAN DISTRO MAYANG MADU PACIRAN LAMONGAN - Ana Fitriyatul Bilgies; Ariefah Sundari; Ali Muhajir; Heni Purnama Putra (Fakultas Ekonomi Universitas Islam Darul Ulum Lamongan, 2021)
The development of the local community and is risen by the end of it would have an impact to an increased the needs of the people , one of these is the credits really needed by the prices of clothing or clothing .This can be traced to looked the more likely side to become a point of significant both as an advance of this business operators take part in the bali distro to meet the needs of the world largest oil consumers clothes paid at the end .Distro Mayang Madu should have received assistance from one seller prices of clothing of the largest memorials in Paciran Lamongan that provides the needs of prices of clothing people in the north coast and the surrounding areas .To win over the competition in the marketing of their products it takes of customers who are a disloyal .Of customers who are a disloyal to putt as well as they would have to re pt indofood acquired misp shares in time to come and inform to others for what is perceived . This study aims to to analyze the influence of the price of , the product quality , as well as the location against customers loyalty Distro Mayang Madu In Paciran Lamongan .Closer look at of this research is descriptive of quantitative .Percent of the population on this research including an in the number of subscribers 400 .The technique of over the withdrawal of funds by smeru within the was used in the study random sampling to the total number of samples from 80 .The technique of the collection of data using the primary data was obtained from the questionnaire that has been tested the validity of and reliabilitasnya .Of the data analysis that is used is identification economic assumptions agreed to at the fit and proper test classical , it is anticipated that analysis linear regression of multiple , the coefficients determined and efforts whatever survives this test a hypothesis with use some help a nice little software you spss .The result of this research showing the price of ( h ) had a positive impact on customers loyalty ( lp ) Distro Mayang Madu In Lamongan .The product quality ( kp ) had a positive impact on customers loyalty ( lp ) Distro Mayang Madu in lamongan .As well as the location ( l ) exert a positive influence against customers loyalty ( lp ) of a Distro Mayang Madu in Lamongan.